AB1053 The Nationwide Danish Rheumatologic Biobank – Paving The Road To Personalized Treatment of Patients with Inflammatory Rheumatic Diseases. (15th July 2016) - Kringelbach, T.; Glintborg, B.; Johansen, J.; Høgdall, E.; Hetland, M.L.
Abstract : Background: The medical treatment of inflammatory rheumatic diseases has improved during the last decades. However, many patients experience treatment failure due to lack of effectiveness or serious adverse events. Biomarkers are promising future tools to predict treatment outcome on the patient level (personalized treatment), but these biomarkers still remain to be identified. The newly started nationwide Danish Rheumatologic Biobank (DRB) provides the infrastructure needed to promote research within this field. The protocol "Identification of biomarkers that improve diagnostics, predict treatment responses, adverse events or prognosis among patients with inflammatory rheumatic disease followed in the Danish nationwide DANBIO registry" (approvals: H-2–2014–086 and GLO-2015–6) is the first national study within DRB. DRB is built on the infrastructure of the Danish CancerBiobank [1] and is funded by The Danish Rheumatism Association and the hospital owners (Danish Regions). Objectives: The aim of DRB is to promote the identification of new biomarkers for personalised treatment of patients with inflammatory rheumatic diseases. We here present the first protocol in DRB. Methods: DRB is established through the collaboration between Depts. of Rheumatology and Depts. Clinical Biochemistry at hospitals in all regions of Denmark. Currently, 9 hospitals participate. Patients are included after having signed an informed consent. Blood samples are collected 1) cross-sectionally (i.e. patients provide one blood sample); 2) longitudinally (i.e. patients are enrolled when they start a new disease-modifying anti-rheumatic drug (DMARD, biologic or conventional synthetic) and provide blood samples at 0, 3, 6, 12, 24, 36, 48 and 60 months and at time of treatment withdrawal. Synovial fluid, tissue and urine may also be collected. Samples are collected, handled and stored (at minus 80 0 C) according to nationally approved Standard Operating Procedures (SOPs) and all data regarding the samples are registered in the nationwide database, the Biobank of Danish Regions. Sample-associated high-quality clinical data are registered prospectively in the nationwide quality and research registry, DANBIO, e.g. patient demographics and patient-reported outcomes, previous and current treatment (DMARDs) including reasons for withdrawal, and physician-reported outcomes (clinical characteristics, treatment response, imaging) [2]. Results: From May 2015 to January 2016, 840 patients with rheumatoid arthritis (67%), axial spondyloarthritis (22%), psoriatic arthritis (9%) and other diagnoses (2%) had been included in the study, and had contributed 1, 239 blood sample packages stored at minus 80 0 C, each including whole blood (1x1.5 ml), buffy coat (1x1.5 ml), EDTA plasma (2x2 ml), serum (4x2 ml) and whole blood in PAXgene RNA tubes (2x2.5 ml). Conclusions: The establishing of DRB has been successful with >1, 200 samples collected. Sampling from patients included in the first biomarker protocol continues and the first scientific results are expected in 2016. DRB is unique due to the nationwide and parallel collection of clinical data and biological material from patients with inflammatory rheumatic diseases. References: www.cancerbiobank.dk Rheumatology (Oxford). 2011 Jan;50(1):69–77 Disclosure of Interest: None declared